Unconventional Electromagnetic Response of Strongly Coupled Nanoparticles in the Thermal Infrared Region: Link with Effective Medium Properties and Incoherent Fields. (15th January 2022) - Guerra, Timothée; De Sousa Meneses, Domingos; Hugonin, Jean‐Paul; Blanchard, Cédric
Abstract: The effective refractive index ( n eff ) of suspensions of subwavelength particles is calculated in resonant domains of the thermal infrared region. On account of strong cooperative effects, notable deviations arise from what is expected for small particles; these features include unusual activation of higher‐order multipoles despite the fact that the system can be homogenized and the manifestation of effective magnetic properties. The former feature leads to fundamental questions about the validity of the homogenization procedure, in particular regarding the meaning of the imaginary part of n eff, that is absorption by the particles and therefore interrogates the degree to which the composite can be unrestrictedly described by an effective dielectric function. The latter feature offers interesting perspectives for the development of nanophotonic devices, based on dielectric subwavelength particles, exhibiting an effective magnetic response. Finally, the study of the coherent and incoherent decomposition of the field allows to demonstrate, counterintuitively, that a material can admit effective optical properties even in the presence of strong incoherent intensities and that the variance of the field over a statistical ensemble of configurations is a misleading indicator of scattering. Abstract : Effective medium theories fail in predicting the properties of nanoparticles in the thermal infrared because of scattering and field fluctuations, shown here to be uncorrelated phenomena. While both lead to unconventional behaviors, an effective refractive index can be extracted through extensive numerical calculations, but with restrictions concerning either its statistical reproducibility over an ensemble of configurations or the nanoparticles' absorption.